IL-4-Producing Vγ1+/Vδ6+ γδ T Cells Sustain Germinal Center Reactions in Peyer’s Patches of Mice - Leon Ullrich (Frontiers Media S.A., 2021)
The mucosal immune system is the first line of defense against pathogens. Germinal centers (GCs) in the Peyer’s patches (PPs) of the small intestine are constantly generated through stimulation of the microbiota. In this study, we investigated the role of γδ T cells in the GC reactions in PPs. Most γδ T cells in PPs localized in the GCs and expressed a TCR composed of Vγ1 and Vδ6 chains. By using mice with partial and total γδ T cell deficiencies, we found that Vγ1+/Vδ6+ T cells can produce high amounts of IL-4, which drives the proliferation of GC B cells as well as the switch of GC B cells towards IgA. Therefore, we conclude that γδ T cells play a role in sustaining gut homeostasis and symbiosis via supporting the GC reactions in PPs.